Water-soluble unit dose articles
Patent Information
- Application Number
- CN202610391375.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-01
- Filing Date
- 2026-03-27
- Publication Date
- 2026-10-16
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] A water-soluble unit-dosage article made from a water-soluble film comprising a water-soluble polymer, wherein the water-soluble polymer comprises a blend of the following substances:
[0002] i) starch; and
[0003] ii) Caseinate polymers. Background Technology
[0004] The demand for innovative packaging solutions has fueled significant interest in the development of water-soluble films, particularly for applications in laundry and automated dishwashing. These films serve as a convenient means of encapsulating detergents, fabric softeners, and other cleaning agents, allowing consumers to use these products in a pre-measured, easy-to-use form. A key requirement for these films is their ability to dissolve effectively in water, thereby facilitating the rapid release of the encapsulating material during the washing process.
[0005] In the field of water-soluble membranes, polyvinyl alcohol (PVA) has been widely used due to its advantageous properties, including good film-forming ability, water solubility, and mechanical strength. However, while PVA-based membranes have been successful in various applications, there is still a desire to find alternative membranes made from natural materials that exhibit good strength and solubility characteristics, especially under cold and rapid and low-wash conditions. Summary of the Invention
[0006] A first aspect of the present invention is a water-soluble membrane comprising a water-soluble polymer comprising a blend of starch and caseinate polymers.
[0007] Surprisingly, the membrane according to the invention exhibits excellent solubility characteristics, superior to starch membranes or caseinate polymer membranes, and superior to membranes comprising caseinate polymers and alternative polysaccharides (such as pectin and alginate). The membrane also exhibits good mechanical properties.
[0008] This invention relates to a water-soluble unit-dose article comprising a water-soluble membrane. The water-soluble membrane comprises a water-soluble polymer, wherein the water-soluble polymer comprises a blend of starch and caseinate polymers. Surprisingly, the membrane according to the invention exhibits excellent solubility characteristics, superior to starch membranes or caseinate polymer membranes, and superior to membranes comprising blends of caseinate polymers and alternative polysaccharides (such as pectin and alginate). The membrane also exhibits good mechanical properties.
[0009] The water-soluble unit-dosage article according to the invention comprises a treatment composition and at least one internal compartment, wherein the treatment composition is contained within the at least one compartment. The treatment composition is selected from laundry detergent compositions, fabric softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof. Detailed Implementation
[0010] Water-soluble membrane
[0011] The water-soluble film comprises a water-soluble polymer, wherein the water-soluble polymer comprises a blend of starch and caseinate polymers. The starch and caseinate polymers are described in more detail below.
[0012] The water-soluble membrane of the present invention is soluble in water.
[0013] The water-soluble membrane preferably has a thickness between 30µm and 150µm, more preferably between 50µm and 100µm, and most preferably between 60µm and 85µm.
[0014] Water-soluble membrane properties :
[0015] As described in column 8, lines 10 through 57 of U.S. Patent No. 7,022,656, according to MonoSol Test Method 205 (MSTM 205), the dissolution time of the water-soluble membrane at 10°C with a thickness of approximately 76 micrometers is preferably less than 90 seconds, preferably less than 60 seconds, and more preferably less than 30 seconds. Preferably, according to MonoSol Test Method 205 (MSTM 205), the dissolution time of the water-soluble membrane at 5°C with a thickness of approximately 76 micrometers is less than 120 seconds, preferably less than 90 seconds, more preferably less than 60 seconds, and even more preferably less than 30 seconds. Preferably, according to MonoSol Test Method 205 (MSTM 205), the disintegration time of the membrane at 10°C with a thickness of approximately 76 micrometers is approximately 40 seconds or less, or approximately 30 seconds or less. Even more preferably, according to MonoSol test method 205 (MSTM 205), the disintegration time of the membrane at a temperature of 5°C and a thickness of about 76 micrometers is about 40 seconds or less, or about 33 seconds or less.
[0016] The membrane disintegration time (I) and membrane dissolution time (S) can be corrected to the standard or reference membrane thickness (76 micrometers) using the exponential algorithms shown in Equations 1 and 2 below, respectively.
[0017] I-calibration = I-measurement × (reference thickness) 2 / Measuring thickness 2 )
[0018] S-correction = S-measurement × (reference thickness)2 / Measuring thickness 2 )
[0019] As measured by the solubility % test method described below, the water-soluble film preferably has a solubility % of 25% or higher, more preferably 35% or higher, more preferably 70% or higher, and even more preferably 80% or higher. Generally, a higher solubility % is desirable to reduce the likelihood of residual film remaining on washed articles subjected to stress washing conditions (e.g., under low water conditions, such as in a washing machine overload) and under cold wash water conditions. Such residues may dissolve upon additional exposure to water, but they may require additional effort from the user and are therefore undesirable.
[0020] Generally, higher tensile strength values are desirable because they will produce stronger water-soluble unit-dose articles. Higher e-modulus values are desirable from the perspective of providing water-soluble unit-dose articles with greater stiffness and a lower likelihood of deformation and adhesion when loaded on top of each other during production. Preferably, when measured at 23°C and 40% RH, the water-soluble film has a tensile strength or stress at break of at least 10 N / mm², preferably between 12 N / mm² and 60 N / mm², more preferably between 14 N / mm² and 60 N / mm², a modulus at at least about 20 N / mm² at 10% elongation, and a stress at at least 12 N / mm² at 100% elongation. Further, the water-soluble film has a tensile strain at break of about 100% to about 1600%, preferably 200% to 1200%, more preferably about 240% to about 800%, as measured in the same manner. When measured at 100°C and 40%RH, the water-soluble membrane exhibits at least approximately 100% of the tensile strain at break, as measured using the same method.
[0021] Preferably, according to OECD 301B testing, the water-soluble membrane and / or water-soluble polymer resin and / or water-soluble polymer alone have a biodegradation rate of at least 60%, preferably at least 65%, more preferably at least 70%, or at least 60%, preferably at least 65%, more preferably at least 70% after 60 days, or after 28 days.
[0022] Preferably, the water-soluble film has a glass transition temperature of less than -5°C and a melt transition temperature of greater than 80°C, as measured by the DSC standard procedure.
[0023] Preferably, the weight ratio of starch to caseinate polymer is 90:10 to 10:90, and more preferably 75:25 to 25:75.
[0024] The water-soluble polymer may be between 50% and 95% by weight of the membrane, preferably between 55% and 90%, and more preferably between 60% and 80%.
[0025] Preferably, the water-soluble film contains a non-aqueous plasticizer. Preferably, the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof. Suitable polyols include those selected from the group consisting of: glycerol, diglycerol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, up to 400 MW of polyethylene glycol, neopentyl glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, and polyether polyols, or mixtures thereof. Suitable sugar alcohols include those selected from the group consisting of: isomaltitol, maltitol, sorbitol, xylitol, erythritol, ribitol, galactitol, pentaerythritol, and mannitol, or mixtures thereof. More preferably, the non-aqueous plasticizer is selected from glycerol, 1,2-propanediol, dipropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, most preferably from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof. A particularly suitable plasticizer system comprises a blend of glycerol, sorbitol, and 2-ethyl-2-hydroxymethyl-1,3-propanediol. Another particularly suitable plasticizer system comprises a blend of glycerol, dipropylene glycol, and sorbitol. Preferably, the film contains between 5% and 50% by weight of the film, preferably between 10% and 40%, more preferably between 20% and 30% of a non-aqueous plasticizer.
[0026] Preferably, the water-soluble film according to the invention comprises a surfactant. Preferably, the water-soluble film comprises a surfactant in an amount between 0.1% and 5% by weight of the water-soluble film, preferably between 1% and 3%. Suitable surfactants may include nonionic, cationic, anionic, amphoteric, and zwitterionic categories. Suitable surfactants include, but are not limited to, polyoxyethyleneized polypropylene glycol, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenols and alkanolamides (nonionic), polyoxyethyleneized amines, quaternary ammonium salts and polyoxyethyleneized quaternary ammoniums (cationic), and amine oxides, N-alkyl betaine and sulfobetaine (zwitterionic). Other suitable surfactants include sodium sulfosuccinate, acylated fatty acid esters of glycerol and propylene glycol, lactams of fatty acids, sodium alkyl sulfate, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, acetylated fatty acid esters, and combinations thereof.
[0027] Preferably, the water-soluble membrane according to the invention comprises a lubricant / stripping agent. Suitable lubricants / stripping agents may include, but are not limited to, fatty acids and their salts, fatty alcohols, fatty acid esters, fatty amines, fatty amine acetates, and fatty amides. Preferred lubricants / stripping agents are fatty acids, fatty acid salts, and fatty amine acetates. The amount of lubricant / stripping agent in the water-soluble membrane is in the range of 0.02% to 1.5%, preferably 0.1% to 1%, based on the weight of the water-soluble membrane.
[0028] Preferably, the water-soluble film comprises fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof. Suitable fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof include, but are not limited to, starch, modified starch, cross-linked polyvinylpyrrolidone, cross-linked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof in the water-soluble film is in the range of 0.1% to 25% by weight of the water-soluble film, preferably 1% to 10%, more preferably 2% to 8%, and most preferably 3% to 5%. In the absence of starch, a preferred range for suitable fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof is 0.1% to 1% by weight of the water-soluble film, preferably 4%, more preferably 6%, even more preferably 1% to 4%, and most preferably 1% to 2.5%.
[0029] Preferably, as measured by Karl Fischer titration, the residual moisture content of the water-soluble membrane according to the invention is at least 4% by weight of the water-soluble membrane, more preferably in the range of 4% to 15%, and even more preferably 5% to 10%. The membrane has been pre-conditioned for 24 hours at 20°C and 60% relative humidity before the residual moisture content is determined.
[0030] Preferably, the water-soluble membrane according to the invention contains an aversive agent, more preferably a bittering agent. Suitable bittering agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, benzyl dinatamide, or mixtures thereof. Any suitable amount of the aversive agent may be used in the membrane. For water-soluble membranes, suitable levels include, but are not limited to, 1 ppm to 5000 ppm, or even 100 ppm to 2500 ppm, or even 250 ppm to 2000 rpm.
[0031] The water-soluble film according to the invention can be opaque, transparent, or translucent. The water-soluble film according to the invention may include a printing area. The printing area can be implemented using standard techniques such as flexographic printing or inkjet printing.
[0032] The water-soluble film or water-soluble unit-dose product, or both, according to the invention can be coated with a lubricant. Preferably, the lubricant is selected from talc, zinc oxide, silicon dioxide, siloxane, zeolite, silicic acid, alumina, sodium sulfate, potassium sulfate, calcium carbonate, magnesium carbonate, sodium citrate, sodium tripolyphosphate, potassium citrate, potassium tripolyphosphate, calcium stearate, zinc stearate, magnesium stearate, starch, modified starch, clay, kaolin, gypsum, cyclodextrin, or mixtures thereof.
[0033] starch
[0034] Starch is a complex carbohydrate found in many plant-based food sources, such as corn, potatoes, wheat, and rice. It consists of long chains of linked glucose molecules. Chemically, starch is composed of two main components: amylose and amylopectin. Amylose is a straight chain of glucose units, while amylopectin is a branched structure with many side chains. The ratio of amylose to amylopectin varies depending on the plant source. Starch is typically extracted from plants by grinding or milling the raw material and then separating the starch granules from other components. The starch can then be further modified. The starch used in this invention is preferably anionicly modified to further improve its water solubility.
[0035] In this article, "anionic modified starch" refers to starch that has been modified and carries a negative charge at a pH above 5.
[0036] The preferred anionic modified starch used in this article is Purity Gum Ultra, available from Ingredion Company. Purity Gum Ultra is a waxy corn starch modified with octenyl succinic anhydride (OSA), whereby the octenyl succinic anhydride reacts with hydroxyl groups to produce an ester and a free carboxylic acid. Purity Gum Ultra has a degree of substitution between about 0.01 and about 0.048. At pH values above the pKa of the carboxylic acid, the starch will be anionic.
[0037] Modified amylose and / or modified amylopectin are represented by the corresponding structures I and II below. Both materials are described in Kirk-Othmer's Encyclopedia of Chemical Technology, 4th edition, Volume 22, pp. 701-703. Starch is generally described on pp. 699-719.
[0038] Structure I
[0039]
[0040] and / or
[0041]
[0042] Structure II
[0043] At least one R in structure I and / or structure II is an anionic group.
[0044] Each R is independently chosen from Ra, Rc, Rp, and R. E and R S The group formed;
[0045] in:
[0046] Each Ra is independently selected from the group consisting of H and C1-C4 alkyl groups;
[0047]
[0048] Where M is a suitable cation selected from the group consisting of: H+, Li+, Na+, K+, 1 / 2Ca2+, 1 / 2Mg2+, barium, zinc and lanthanum (III), or +NHjRk, where j and k are independently from 0 to 4, and where j+k is 4, and R in the formula is any part capable of forming a cation, such as methyl and / or ethyl groups or derivatives.
[0049]
[0050] Each R H Choose independently the group consisting of Ra and Rc;
[0051] Each x is from 1 to approximately 5;
[0052] n is the number that causes the polymer to have the weight-average molecular weight according to the invention;
[0053] And each of R E for
[0054]
[0055] R1, R2, and R3 are independently selected from H, C1-C18 alkyl, C1-C18 alkylene, and M is a suitable cation selected from the group consisting of H+, Li+, Na+, K+, 1 / 2Ca2+, 1 / 2Mg2+, barium, zinc, and lanthanum(III), or +NHjRk, where j and k are independently from 0 to 4, and j+k is 4, and R in the formula is any part capable of forming a cation, such as methyl and / or ethyl groups or derivatives;
[0056] And each of Rs is
[0057]
[0058] Each of R1, R2, R3 and R4 is independently selected from H, C1-C18 alkyl, C1-C18 alkylene, wherein M is a suitable cation selected from the group consisting of: H+, Li+, Na+, K+, 1 / 2Ca2+, 1 / 2Mg2+, barium, zinc and lanthanum(III), or +NHjRk, wherein j and k are independently from 0 to 4, and wherein j+k is 4, and R in the formula is any part capable of forming a cation, such as methyl and / or ethyl groups or derivatives.
[0059] In one example, the precursor starch is unsubstituted, and therefore R equals H in structures I and II. After the precursor starch is modified, each R is independently chosen from Ra, Rc, Rp, and R. E and R S The group consists of at least one R group that is an anionic group.
[0060] Group R E The degree of substitution (“DS”), sometimes abbreviated as “DSE” in this document, refers to the number of R groups substituted for each anhydrous D-glucose unit. E The number of moles of the components, wherein the anhydrous D-glucose unit is a six-membered ring as shown in the repeating unit of the general formula above.
[0061] The "degree of substitution" of the group Rc, sometimes abbreviated as "DSC" in this document, refers to the number of moles of the group Rc component that are substituted for each anhydrous D-glucose unit, where the anhydrous D-glucose unit is a six-membered ring as shown above in the repeating unit of the general formula.
[0062] The “degree of substitution” of the group Ra, which is sometimes abbreviated as “DSA” in this document, refers to the number of moles of the group Ra component that are substituted for each anhydrous D-glucose unit, wherein the anhydrous D-glucose unit is a six-membered ring as shown in the repeating unit of the general formula above.
[0063] The “degree of substitution” of the group Rp, which is sometimes abbreviated as “DSP” in this document, refers to the number of moles of the group Rp component that are substituted for each anhydrous D-glucose unit, wherein the anhydrous D-glucose unit is a six-membered ring as shown in the repeating unit of the general formula above.
[0064] Group R S The "degree of substitution," sometimes abbreviated as "DSS" in this article, refers to the number of R groups substituted for each anhydrous D-glucose unit. S The number of moles of the components, wherein the anhydrous D-glucose unit is a six-membered ring as shown in the repeating unit of the general formula above.
[0065] Preferably, the total average degree of substitution of the anionic modified starch is from 0.01 to 3.0, and more specifically from 0.01 to 0.32.
[0066] Preferably, the anionic modified starch has an average degree of substitution of anionic groups of 0.01 to 3.0, and more specifically 0.01 to 0.32.
[0067] Preferably, the anionic modified starch has an average MW of 100 kDa to 100,000 kDa, depending on the treatment process during separation, such as “acid thinning” or enzymatic degradation.
[0068] Preferably, the anionic modified starch has an amylose / amylose ratio of 1 / 99 (waxy starch) to 27 / 73 (natural dent corn) or 50 / 50 to 70 / 30 (high amylose corn), and a ratio between 70 / 30 and 1 / 99, depending on the starch source, such as corn, wheat, potato, cassava, etc. Preferably, the amylose and amylopectin are randomly arranged.
[0069] "Modified starch" is starch that has been modified chemically or enzymatically. Modified starch contrasts with natural starch, which has not been chemically or otherwise modified. Chemical modification may also involve derivatizing starch by reacting the hydroxyl groups of starch with alkylene oxides and other ethers, esters, polyurethanes, carbamates, or isocyanates. Hydroxyalkyl, acetyl, or carbamate starches, or mixtures thereof, can be used as chemically modified starches. Biological modification of starch may include bacterial digestion of carbohydrate bonds or enzymatic hydrolysis using enzymes such as amylases, amylopectinases, etc.
[0070] Generally, all types of natural starch can be used in this invention. Suitable naturally occurring starches include, but are not limited to: corn starch, potato starch, sweet potato starch, wheat starch, sago palm starch, tapioca starch, rice starch, soybean starch, bamboo taro starch, amylopectin starch, fern starch, lotus root starch, waxy corn starch, and high amylose corn starch. Naturally occurring starches, especially corn starch and wheat starch, are particularly beneficial due to their low cost and availability.
[0071] Precursor starches, which can have a lower weight-average molecular weight than natural starches, can be modified to further reduce their weight-average molecular weight. The degree of modification varies depending on the application; generally, the greater the degree of substitution, the less retrogradation occurs compared to natural, unsubstituted starches. Starches with high amylose content are more prone to retrogradation, and therefore, modification with high amylose content is particularly beneficial in preventing retrogradation.
[0072] Preferably, the starch precursor is further chemically modified with octenyl succinic anhydride.
[0073] Caseinate polymers
[0074] Casein is a milk-derived protein that is relatively insoluble in water. It is typically obtained by precipitation after adding acid (casein acid) or rennet (enzyme chymotrypsin). Casein salts are defined as salts of casein; their counterions are typically selected from the group consisting of calcium, potassium, ammonium, magnesium, and sodium, or mixtures thereof, with sodium being the most preferred.
[0075] The water-soluble film according to the invention comprises a water-soluble polymer comprising a blend of a caseinate polymer and starch, wherein the caseinate polymer is preferably selected from an alkali metal salt of caseinate, more preferably sodium caseinate.
[0076] Although it is stated that the polymer according to the invention comprises caseinate, in practice, the caseinate will be a mixture of caseinate and casein impurities. The relative weight ratio of casein impurities to caseinate is a function of the pH of the water-soluble membrane. Therefore, when tyrosine salts are referred to herein, this encompasses pure sodium caseinate as well as certain levels of casein impurities.
[0077] Unwilling to be bound by theory, casein is composed of a(s1)-, a(s2)-, β-, and κ-casein. Like any protein, casein is made up of hundreds of individual amino acids, each of which can carry a positive or negative charge, depending on the pH of the surrounding system. At certain pH values, all the positive and negative charges on casein are balanced (i.e., the net charge on the protein is zero); this pH value is known as the isoelectric point (IEP), and the isoelectric point of casein is 4.6. The IEP is the pH at which proteins are least soluble. Therefore, to make casein soluble, it is used in the form of casein salts, as alkaline conditions make casein soluble.
[0078] Preferably, the water-soluble polymer is present in 60% to 80% by weight of the water-soluble film according to the invention, and is composed of a mixture of starch and caseinate polymers.
[0079] Methods of making membranes
[0080] The water-soluble film according to the invention can be formed by blending and co-casting a starch and caseinate polymer of the type and amount described herein with a preferred and optional second additive described herein in a casting solution. If the polymer is mixed first, the water-soluble film is preferably formed by casting the resulting mixture (e.g., together with other plasticizers and other additives) to form a film. Another feature is that the water-soluble film is formed by extrusion, such as blow molding. Most preferably, the water-soluble film according to the invention is prepared by solvent casting.
[0081] Water-soluble unit dose products
[0082] This invention relates to a water-soluble unit-dose article comprising the aforementioned water-soluble membrane, a treatment composition, and at least one internal compartment in which the treatment composition is contained. The treatment composition is described in more detail below.
[0083] The water-soluble unit-dose article includes a water-soluble membrane shaped such that the unit-dose article includes at least one internal compartment surrounded by the water-soluble membrane. The unit-dose article may include a first water-soluble membrane and a second water-soluble membrane sealed to each other to define the internal compartment. The water-soluble unit-dose article is configured such that the treatment composition does not leak out of the compartment during storage. However, when the water-soluble unit-dose article is added to water, the water-soluble membrane dissolves, releasing the contents of the internal compartment into the washing liquid.
[0084] A compartment should be understood as a sealed internal space within a unit dose of the product, which holds the detergent composition. During manufacturing, a first water-soluble film may be formed into an open compartment into which the treatment composition is added. A second water-soluble film is then covered over the first film in an orientation near the opening of the compartment. The first and second films are then sealed together along a sealing region. Sealing may be performed after solvent sealing, heat sealing, or a combination thereof. The preferred sealing solvent is water.
[0085] A unit-dose article may include more than one compartment, or even at least two compartments, or even at least three compartments. The compartments may be arranged in a superimposed orientation, i.e., one positioned on top of another. In this orientation, the unit-dose article will comprise three layers: a top, a middle, and a bottom film. Alternatively, the compartments may be positioned in a side-by-side orientation, i.e., one immediately adjacent to another. The compartments may even be arranged in a "tire and rim" orientation, i.e., the first compartment is positioned close to the second compartment, but the first compartment at least partially encloses the second compartment, but not completely. Alternatively, one compartment may be completely enclosed within another compartment.
[0086] The unit dose article comprises at least two compartments, one of which may be smaller than the other. The unit dose article comprises at least three compartments, two of which may be smaller than the third. The unit dose article comprises at least four compartments, at least three of which may be smaller than the fourth, and preferably the smaller compartments are stacked on top of the larger compartments. The stacked compartments are preferably arranged side-by-side.
[0087] Preferably, the water-soluble unit dose article includes at least two compartments, more preferably at least three compartments, even more preferably at least four compartments, and most preferably wherein the water-soluble unit dose article includes a first compartment and at least a second compartment stacked on the first compartment, more preferably including at least a third compartment oriented in parallel with respect to the second compartment, and the second and third compartments stacked on the first compartment, and even more preferably including at least a fourth compartment oriented in parallel with respect to the second and third compartments, and the second, third, and fourth compartments stacked on the first compartment.
[0088] In a multi-compartment orientation, the detergent composition may be contained in at least one of the compartments. It may be contained, for example, in only one compartment, or in two compartments, or even in three compartments, or even in all available compartments.
[0089] Each compartment may contain the same or different compositions. The different compositions may all be in the same form, or they may be in different forms.
[0090] A water-soluble unit dose product may include at least two internal compartments, wherein a detergent composition is contained in at least one of the compartments, preferably wherein the unit dose product includes at least three compartments, wherein a detergent composition is contained in at least one of the compartments.
[0091] A water-soluble unit-dose product according to the invention may include at least one water-soluble membrane according to the invention. Alternatively, a water-soluble unit-dose product according to the invention may include at least two or even at least three water-soluble membranes according to the invention. Alternatively, a water-soluble unit-dose product according to the invention may include only water-soluble membranes according to the invention, i.e., excluding any water-soluble membranes beyond the scope of the invention. Preferably, the water-soluble single-compartment unit-dose product or water-soluble multi-compartment unit-dose product forming multiple compartments is a side-by-side configuration, wherein the bottom water-soluble membrane and the top water-soluble membrane encapsulating the single compartment are both water-soluble membranes according to the invention. Alternatively, the top water-soluble membrane or the bottom water-soluble membrane is according to the invention. A water-soluble unit-dose product may be formed as compartments having a stacked configuration. In this configuration, each of the top, bottom, and middle water-soluble membranes may be a water-soluble membrane according to the invention. Alternatively, a single water-soluble film, such as only the middle water-soluble film, or only the top water-soluble film, or only the bottom water-soluble film, or any combination of these water-soluble films, may be a water-soluble film according to the invention, while the remaining water-soluble films are outside the scope of the invention. Preferably, all water-soluble films included in the water-soluble unit dose article are water-soluble films according to the invention. These water-soluble films according to the invention may be chemically and physically identical, or alternatively may be chemically and / or physically different. The term "different" means that the first water-soluble film is intended to have at least one chemical and / or physical property that differs from that of the second water-soluble film. This property can be achieved by selecting different polymer resins, which differ, for example, in terms of average individual polymer solution viscosity, average individual polymer hydrolysis degree, the ratio between the first and second water-soluble polymers, or their mixing. "Target average value" takes into account standard polymer variations inherent in any manufacturing process. Alternatively, this property can be achieved by changing the relative content of individual components within the water-soluble film, such as polymer resins, relative to plasticizer or water content, or even changing the exact chemical properties of the additives. Prior to deformation, assess the “different” properties of the initial membrane, for example, in which differences in water-soluble membrane content due to deformation operations, exposure to the encapsulated detergent composition, exchange of active substances between the membrane and the detergent composition, and exchange of active substances with the surrounding storage environment are excluded.
[0092] Treatment composition
[0093] The treatment composition is selected from laundry detergent compositions, fabric softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, preferably laundry detergent compositions, preferably liquid, powder, or mixtures thereof, preferably liquid compositions.
[0094] The term liquid includes gels, solutions, dispersions, pastes, or mixtures thereof.
[0095] The term "powder" herein refers to a treatment composition that may contain solid particles or may be a single homogeneous solid. Preferably, the powder treatment composition contains particles. This means that the powder treatment composition contains individual solid particles, unlike a solid that is a single homogeneous solid. The particles may be free-flowing or compacted, preferably free-flowing.
[0096] Preferably, the treatment composition is a laundry detergent composition, and most preferably a liquid laundry detergent composition.
[0097] The laundry detergent composition can be used in hand washing operations or in automatic machine washing operations, preferably in automatic machine washing operations.
[0098] Preferably, the treatment composition comprises a non-soap surfactant, wherein the non-soap surfactant includes anionic non-soap surfactants and nonionic surfactants. Preferably, the treatment composition comprises between 10% and 60% by weight of the treatment composition, more preferably between 20% and 55% of the non-soap surfactant.
[0099] The weight ratio of non-soap anionic surfactant to nonionic surfactant can be 1:1 to 20:1, preferably 1.25:1 to 17.5:1, 1.5:1 to 15:1, or 1.75:1 to 13:1, or 2:1 to 10:1.
[0100] Preferably, the non-soap anionic surfactant comprises linear alkylbenzene sulfonates, alkyl sulfates, or mixtures thereof. The weight ratio of the linear alkylbenzene sulfonate to the alkyl sulfate is 1:2 to 9:1, preferably 1:1 to 7:1, more preferably 1:1 to 5:1, and most preferably 1:1 to 4:1.
[0101] An example linear alkylbenzene sulfonate is C 10 -C 16 Alkylbenzenesulfonic acid, or C 11 -C 14 Alkylbenzene sulfonic acids. The term "straight-chain" in this document refers to alkyl groups that are straight-chain. Alkylbenzene sulfonates are well known in the art.
[0102] Alkyl sulfate anionic surfactants may comprise alkoxylated alkyl sulfates or non-alkoxylated alkyl sulfates or mixtures thereof. Aloxylated alkyl sulfate anionic surfactants are preferably ethoxylated alkyl sulfate anionic surfactants.
[0103] Alkyl sulfate anionic surfactants may include ethoxylated alkyl sulfate anionic surfactants, preferably having a molar average degree of ethoxylation of 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.
[0104] The alkyl sulfate anionic surfactant may comprise non-ethoxylated alkyl sulfates and ethoxylated alkyl sulfates, wherein the molar average degree of ethoxylation of the alkyl sulfate anionic surfactant is 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.
[0105] The alkyl fraction of anionic alkyl sulfate surfactants may preferably be derived from fatty alcohols, carbonyl synthetic alcohols, Guerbert alcohols, or mixtures thereof.
[0106] Preferably, the treatment composition comprises between 10% and 50% by weight of the treatment composition, more preferably between 15% and 45%, even more preferably between 20% and 40%, and most preferably between 30% and 40%.
[0107] Preferably, the nonionic surfactant is selected from alcohol alkoxylates, carbonyl synthetic alcohol alkoxylates, Gelbert alcohol alkoxylates, alkylphenol alcohol alkoxylates, or mixtures thereof.
[0108] The treatment composition preferably contains between 0.01% and 25% by weight of the treatment composition, more preferably between 1% and 22.5%, more preferably between 5% and 20%, and most preferably between 8% and 20%.
[0109] Preferably, the treatment composition comprises between 0.5% and 20% by weight of the treatment composition, more preferably between 1% and 15%, even more preferably between 1.5% and 10%, and most preferably between 2% and 8%, a soap, preferably a fatty acid salt, more preferably an amine-neutralized fatty acid salt, wherein the amine is preferably an alkanolamine, more preferably selected from monoethanolamine, diethanolamine, triethanolamine or mixtures thereof, and more preferably monoethanolamine.
[0110] Preferably, the treatment composition is a liquid treatment composition; more preferably, the liquid treatment composition contains less than 15%, more preferably less than 13%, even more preferably 1% to 12%, and most preferably 5% to 12% water by weight of the liquid treatment composition.
[0111] Preferably, the treatment composition is a liquid treatment composition comprising a non-aqueous solvent selected from 1,2-propanediol, dipropylene glycol, tripropylene glycol, glycerol, sorbitol, polyethylene glycol, or mixtures thereof. Preferably, the liquid treatment composition comprises between 10% and 40%, more preferably between 15% and 30% by weight of the liquid treatment composition.
[0112] Preferably, the treatment composition contains a fragrance.
[0113] Preferably, the treatment composition comprises auxiliary ingredients selected from the group consisting of: enzyme-based detergents, citrates, bleaching agents, bleaching catalysts, dyes, tinting dyes, brighteners, cleaning polymers including alkoxylated polyamines and polyethyleneimine, detergency polymers, surfactants, solvents, dye transfer inhibitors, chelating agents, encapsulated fragrances, polycarboxylate esters, structural agents, pH adjusters, and mixtures thereof.
[0114] Those skilled in the art will know how to formulate and prepare suitable treatment compositions using known knowledge and techniques. Treatment compositions may contain common detergent ingredients, including surfactants, polymers, bleaching agents, enzymes, fragrances, dyes, structural agents, fillers, water, or mixtures thereof.
[0115] Those skilled in the art will know the known techniques for preparing the water-soluble unit dose product according to the present invention.
[0116] Example
[0117] starch
[0118] The solubility percentage of three bio-based water-soluble membranes was measured using the test methods described below. Membrane 1 was based on a water-soluble caseinate polymer. Membrane 2 was based on a water-soluble starch. Membrane 3 was based on a 50 / 50 blend of caseinate polymer and starch by weight. The data summarized in Table 1 show the synergistic solubility percentage of the blends.
[0119] Table 1: Solubility % of water-soluble membranes
[0120]
[0121] The membrane is too fragile, causing it to break when the solution band is removed, making it impossible to measure the solubility percentage.
[0122] Method for preparing water-soluble membranes
[0123] A solution of 30 wt% active polysaccharide or 100 wt% active caseinate polymer or a 50 / 50 blend by weight (citrus peel pectin from Sigma Aldrich, sodium alginate from VWR, anionic modified starch (Purity Gum Ultra) from Irrian, and sodium caseinate from Thermo Fisher Scientific) was prepared in softened water, wherein each polymer contained 27% glycerol. The solution was mixed at 70°C for at least 4 hours to obtain a homogeneous solution, and then allowed to stand overnight at room temperature to allow for degassing before casting. The solution was poured into a thin layer on a PET casting plate through a film coater with a wet gap in the range of 250 μm to 350 μm, and the thin layer was dried overnight at room temperature and 35% rH. The resulting membrane contained 66 wt% water-soluble polymer resin, 28 wt% glycerol plasticizer system, and 6% water. Individual membrane thicknesses are summarized in Table 2 below.
[0124] Table 2: Film Thickness
[0125]
[0126] Dissolution % test method :
[0127] In this dissolution chamber residue testing method, for each membrane to be tested, three test samples are cut from a selected test membrane with a thickness of approximately 80 µm using a cutting punch. If cutting from a membrane web produced by a continuous method, the samples should be cut from web areas that are evenly spaced along the transverse direction of the web (i.e., perpendicular to the longitudinal direction), if applicable. The membrane sample weight is weighed and tracked by testing. The initial membrane weight (Fo) is recorded. For each sample, a set of two ultrasonically treated, cleaned, and dried sieves is weighed and tracked by testing such that all samples have similar initial weights (within 10% variation). The initial sieve weight is recorded (therefore, for two sets of sieves, total — So). The sample dissolution chamber is assembled by clamping the membrane sample flat between the centers of the two sieves, followed by the assembly of two rubber gaskets (one gasket on each side between the sieve and the gasket), and then two more gaskets. The dissolution chamber assembly is secured with four binding clips evenly spaced around the gaskets and the clips folded back away from the sieves. Fill a beaker with 1,500 ml of RO water (e.g., softened water) at laboratory room temperature (5°C + / - 1°C) and record this room temperature. Set a timer to a specified immersion time of 10 minutes. Place the dissolution chamber assembly in the beaker and immediately start the timer, inserting the dissolution chamber assembly into the water surface at an approximately 45-degree entry angle. This entry angle helps remove air bubbles from the chamber. Position the dissolution chamber assembly at the bottom of the beaker so that the test sample membrane is horizontally positioned approximately 10 mm from the bottom. The four fold-back clamps of the dissolution chamber assembly are adapted to maintain a membrane gap of approximately 10 mm from the bottom of the beaker; however, any other equivalent support components can be used. At the end of 10 minutes, slowly remove the dissolution chamber assembly from the beaker at approximately a 45-degree angle. Hold the dissolution chamber assembly horizontally above the pre-weighed aluminum pan to catch any drips from the screen and carefully remove the clamps, gaskets, and rubber gaskets. Do not open the clamped screen. Place the clamped screen (i.e., screen / residual undissolved membrane / screen) above the aluminum tray and place it in an oven at 100°C for 30 minutes to dry. Weigh the dried clamped screen, including any residual undissolved membrane, and the aluminum tray. Subtract the weight of the aluminum tray and record the final weight of the clamped screen (collectively referred to as Sf, including dried membrane droplets). Calculate the percentage of residue remaining in the membrane sample (“DC residue”):
[0128] DC residue = 100 × ((Sf-So) / F0)
[0129] Therefore, the percentage of dissolution equals 100% minus the residue.
[0130] The dimensions and values disclosed herein should not be construed as strictly limited to the precise numerical values cited. Rather, unless otherwise specified, each such dimension is intended to represent the stated value and the range surrounding its functional equivalent. For example, a dimension disclosed as “40 mm” is intended to represent “approximately 40 mm”.
Claims
1. A water-soluble unit-dose article comprising a water-soluble membrane, a treatment composition, and at least one internal compartment, wherein the treatment composition is contained within the at least one internal compartment, the treatment composition being selected from laundry detergent compositions, fabric softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, wherein the water-soluble membrane comprises a water-soluble polymer, wherein the water-soluble polymer comprises a blend of the following substances: i) starch; and ii) Caseinate polymers, The water-soluble polymer is between 50% and 95% by weight of the membrane, and the weight ratio of the starch to the caseinate polymer is between 90:10 and 10:
90.
2. The water-soluble unit dose product according to claim 1, wherein the weight ratio of the starch to the caseinate polymer is from 75:25 to 25:
75.
3. The water-soluble unit dose product according to any one of claims 1 or 2, wherein the caseinate polymer is selected from alkali metal salts of caseinate, preferably sodium caseinate.
4. The water-soluble unit dose product according to any one of the preceding claims, wherein the starch is anionic modified starch.
5. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble polymer comprises between 50% and 95% by weight of the film, preferably between 55% and 90%, and more preferably between 60% and 80%.
6. The water-soluble unit-dosage article according to any one of the preceding claims, wherein the film comprises a non-aqueous plasticizer, preferably wherein the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof, more preferably from glycerol, 1,2-propanediol, trimethylolpropane, dipropylene glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-hydroxymethyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, most preferably from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof, preferably wherein the film comprises between 5% and 50% by weight of the film, preferably between 10% and 40%, more preferably between 20% and 30% of the non-aqueous plasticizer.
7. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble film comprises a surfactant in an amount between 0.1% and 5%, preferably between 1% and 3%, based on the weight of the water-soluble film.
8. The water-soluble unit dose product according to any one of the preceding claims, wherein for a 76-micrometer-thick film, according to MSTM-205 at 5°C, the film has a dissolution time of less than 120 seconds, preferably less than 90 seconds, and more preferably less than 60 seconds.
9. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble membrane contains a residual moisture content of at least 4%, more preferably 4% to 15%, and even more preferably 5% to 10% by weight of the membrane, as measured by Karl Fischer titration.
10. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble film has a thickness between 30µm and 150µm, preferably between 50µm and 100µm, and most preferably between 60µm and 85µm.
11. A method for producing a membrane of a water-soluble unit dose article according to any one of the preceding claims, the method comprising the steps of: i) Dissolve caseinate polymer, starch and optional additives in water to form an aqueous solution; as well as ii) Cast the solution obtained in step i) into a film.
12. The water-soluble unit-dosage article according to any one of claims 1 to 10, wherein the membrane has a solubility of 25% or higher, preferably 70% or higher, as measured by the solubility % test method described herein.
13. The water-soluble unit dose article according to any one of claims 1 to 10 or 12, wherein the treatment composition is a liquid, powder or mixture thereof, preferably a liquid laundry detergent composition.
14. The water-soluble unit-dosage article according to any one of claims 1 to 10 or 12 to 13, wherein the treatment composition comprises a non-soap surfactant, wherein preferably, the non-soap surfactant is selected from anionic non-soap surfactants, nonionic surfactants, and mixtures thereof, wherein preferably, the treatment composition comprises between 10% and 60% by weight of the treatment composition, more preferably between 20% and 55% of the non-soap surfactant.
15. The water-soluble unit dose article according to any one of claims 1 to 10 or 12 to 14, wherein the treated composition comprises less than 15%, preferably less than 13%, more preferably between 1% and 12%, and most preferably 5% to 12% water by weight of the treated composition.
16. The water-soluble unit-dose article according to any one of claims 1 to 10 or 12 to 15, wherein the treated composition comprises between 10% and 40%, preferably between 15% and 30% by weight of the treated composition.
Citation Information
Patent Citations
Water-soluble copolymer film packet
US7022656B2